Forest regeneration pathways in contrasting deforestation patterns of Amazonia - Alencar, Lucas; Escada, Maria Isabel Sobral; Camargo, José Luís Campana (Frontiers in Environmental Science, 2023)
Secondary vegetation is increasingly recognized as a key element for biodiversity conservation and carbon stocks in human-modified landscapes. Contrasting deforestation patterns should lead to distinct patterns of forest regeneration, but this relationship is yet to be unveiled for long-term studies. Using Landsat data from 1985 to 2015, we analyzed the surface area, spatial distribution, and age of secondary vegetation in Fishbone and Geometric patterns of deforestation. Additionally, we investigated to which extent secondary vegetation reduces forest patch isolation at the landscape level across time. We found the Fishbone pattern to consistently have more secondary vegetation over time than the Geometric pattern, despite having the same size of the deforested area. However, the Fishbone pattern showed more secondary vegetation area with less than five years old, while the Geometric pattern showed more area with secondary vegetation with more than 30 years old. Regarding spatial distribution, we found secondary vegetation to be more spread across the entire landscape at the Fishbone pattern and to consistently reduce forest patch isolation across time. This is congruent with the land use typically found in Geometric (industrial cropping and ranching) and Fishbone (fallow agriculture with small-scale ranching) patterns. These findings indicate that the Fishbone pattern of deforestation produces a more biodiversity-friendly landscape structure than the Geometric pattern. On the other hand, older secondary vegetation found in the Geometric deforestation pattern could indicate more carbon stocked in those landscapes. Future public policies of land use and occupation should consider better landscape planning and management to overcome this duality and create synergies between biodiversity conservation and secondary vegetation carbon stock.